THE INFLUENCE OF ATTITUDE AND INDIVIDUAL CHARACTERISTICS ON ENTREPRENEURIAL INTENTIONS OF STUDENTS, FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY - Ukufah, Nur Aini Aprillia; Sudiarditha, I Ketut R; Pratama, Aditya (Yayasan Education and Social Center, 2024)
This study aims to determine and analyze the influence of attitudes and individual characteristics on entrepreneurial intentions among students at the Faculty of Economics, Universitas Negeri Jakarta. In this research, the Proportional Random Sampling technique was used which resulted involved 399 active students from the Faculty of Economics, Universitas Negeri Jakarta, class of 2019, as the research sample. The research method employed in this study is quantitative research with a survey research design. The data analysis technique used is multiple regression analysis with IBM SPSS 27 software. The results of this study indicate that attitude has a positive and significant effect on entrepreneurial intentions among students, and individual characteristics also have a positive and significant effect on students' entrepreneurial intentions. Additionally, both attitude and individual characteristics have a simultaneous effect on students' entrepreneurial intentions. Attitude and individual characteristics have an influence of 82.8% Against Student Entrepreneurial Intentions